Management of hypospadias in a resource-poor setting: the Ibadan experience (2018)
Background: Penile anomalies especially hypospadias are one of the most common genitourinary anomalies seen in newborns, and they pose a great deal of psychological stress to their mothers. This study examined our experience in the management of hypospadias. Patients: and Methods A retrospective study of all patients (Group A) managed for hypospadias from 2004 to 2013 was conducted. Data obtained included patients’ demography, their clinical presentation and management. These were analysed and compared with a similar study (Group B) conducted in this hospital four decades earlier between 1966 and 1977. Results: Forty-eight patients belonging to Group A had repair of hypospadias in comparison to the 42 patients in Group B. The mean age at presentation in Group A was 2.7 ± 4 years, and the anomaly was discovered at birth in all the patients. In contrary, Group B had 32 (76.2%) patients who presented immediately after birth and 10 (23.8%) patients who were either adolescents or adults (12-36 years) with a mean age of 18.9 years. Anterior hypospadias occurred more commonly in both groups; 10 (20.8%) patients were circumcised in Group A and 4 (9.5%) patients in Group B. Surgical site infection was the most common post-operative complication observed in both groups. The type of surgical repair was observed to have significantly influenced the outcome of surgical repair in patients in Group A (j2 = 14.13, P = 0.05). Conclusion: Proper and successful management of hypospadias can be enhanced in this environment with adequate media advocacy directed at prompt recognition of this anomaly and avoidance of circumcision when hypospadias has been identified.